STUDI PREVALENSI KERACUNAN PESTISIDA PADA PETANI PENYEMPROT SAYUR DI DESA MENDONGAN KECAMATAN SUMOWONO KABUPATEN SEMARANG - Muhammad Imam Ma'arif; Suhartono Suhartono; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Mendongan village is one of the producers of vegetables in the use of pesticides are still high, of which 100% of the farmers in the village Mendongan use pesticides to kill pests. Results of preliminary studies, 75% of farmers do not use full protective equipment when spraying vegetables. In Semarang District also has been no monitoring of pesticide poisoning by the District Health Office and there has been no thorough assistance of puskesmas officers related to the use of pesticides by farmers. The purpose of this study was to determine the prevalence of pesticide poisoning in spraying vegetable farmers in the village Mendongan Sumowono District of Semarang District. The research location is in the village Mendongan Sumowono District of Semarang District. This study was observational analytic with cross sectional study design. Samples of this study were 38 respondents. Data analysis using Chi Square. The results showed a 44.7% level of knowledge is not good, the frequency of spraying 5.3% often, completeness APD 31.6% of respondents did not complete, 97.4% of respondents working lives long, long hose down 26.3%> 3 hours a day, spraying 2.6% one time, the dose of pesticides used 28.9% of respondents do not match, the wind direction while spraying 5.3% in the opposite direction, and the amount of pesticides 31.6%> 3 types. Cholinesterase level examination results showed 100% of respondents are still in a state of normal. The result of the relationship of nine independent variables studied there is no meaningful relationship to lower levels of cholinesterase in the blood of farmers, but based on the value of RP (Prevalence Ratio) when spraying (PR = 1.768; 95% CI = 1.330 to 2.334) and wind direction (PR = 1.800; 95% CI = 1.344 to 2.411) are risk factors for low levels of cholinesterase. The conclusion from this study that the prevalence of poisoning in spraying vegetable farmer in the village Mendongan Sumowono District of Semarang District of 0.